2024
DOI: 10.1186/s12872-024-03804-3
|View full text |Cite
|
Sign up to set email alerts
|

Causality of the gut microbiome and atherosclerosis-related lipids: a bidirectional Mendelian Randomization study

Da Teng,
Wenjuan Jia,
Wenlong Wang
et al.

Abstract: Aims Recent studies have indicated an association between intestinal flora and lipids. However, observational studies cannot indicate causality. In this study, we aimed to investigate the potentially causal relationships between the intestinal flora and blood lipids. Methods We performed a bidirectional two-sample Mendelian Randomization (MR) analysis to investigate the causal relationship between intestinal flora and blood lipids. Summary statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Mendelian randomization studies in two samples suggested that complex networks may exist among gut microbes, and interactions between bacteria, viruses, and fungi jointly influence the occurrence and progression of atherosclerosis ( Jiang et al, 2024 ). Desulfovibrioceae showed a stable and significant negative correlation with ApoB levels ( Teng et al, 2024 ), which was associated with increased TG levels ( Takeda et al, 2023 ). The traditional Chinese herbal prescription ( Yu et al, 2024 ), serum sex hormones ( Peters et al, 2023 ), and structure of the gut virome ( Li et al, 2024c ) play an important role in slowing down the progression of atherosclerosis by regulating altered intestinal microbiota and perturbed metabolites.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Mendelian randomization studies in two samples suggested that complex networks may exist among gut microbes, and interactions between bacteria, viruses, and fungi jointly influence the occurrence and progression of atherosclerosis ( Jiang et al, 2024 ). Desulfovibrioceae showed a stable and significant negative correlation with ApoB levels ( Teng et al, 2024 ), which was associated with increased TG levels ( Takeda et al, 2023 ). The traditional Chinese herbal prescription ( Yu et al, 2024 ), serum sex hormones ( Peters et al, 2023 ), and structure of the gut virome ( Li et al, 2024c ) play an important role in slowing down the progression of atherosclerosis by regulating altered intestinal microbiota and perturbed metabolites.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%